Pengaruh Kecerdasan Emosional dan Kecerdasan Spiritual dengan Kecerdasan Intelektual sebagai Variabel Moderasi terhadap Perilaku Etis Mahasiswa Akuntansi : (Studi Empiris pada Mahasiswa Program Studi Akuntansi Universitas Nusa Nipa) - Victoria Adriyani Bota; Wilhelmina Mitan; Emilianus Eo K. Goo (Universitas 45 Surabaya, 2024)
This research aims to analyze the influence of emotional intelligence and spiritual intelligence with intellectual intelligence as a moderating variable on the ethical behavior of accounting students. This type of research is quantitative research with an associative approach. The sampling technique uses purposive sampling, a type of Stratified random sampling method, where sampling is carried out and determined using certain consideration techniques and criteria with a sample size of 72 people. The data collection technique used a questionnaire (google form) which was distributed to 72 respondents. Data analysis used multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS) version 26. The results of this study indicate that partially emotional intelligence and spiritual intelligence have a significant effect on the ethical behavior of accounting students. Meanwhile, from the MRA test results, intellectual intelligence cannot moderate the influence of emotional intelligence or spiritual intelligence on the ethical behavior of accounting students.